Sex Difference and Rupture Rate of Intracranial Aneurysms: An Individual Patient Data Meta-Analysis. Issue 2 (February 2022) - Zuurbier, Charlotte C.M.; Molenberg, Rob; Mensing, Liselore A.; Wermer, Marieke J.H.; Juvela, Seppo; Lindgren, Antti E.; Jääskeläinen, Juha E.; Koivisto, Timo; Yamazaki, Tomosato; Uyttenboogaart, Maarten; van Dijk, J. Marc C.; Aalbers, Marlien W.; et al.
Abstract : Background and Purpose: In previous studies, women had a higher risk of rupture of intracranial aneurysms than men, but female sex was not an independent risk factor. This may be explained by a higher prevalence of patient- or aneurysm-related risk factors for rupture in women than in men or by insufficient power of previous studies. We assessed sex differences in rupture rate taking into account other patient- and aneurysm-related risk factors for aneurysmal rupture. Methods: We searched Embase and Pubmed for articles published until December 1, 2020. Cohorts with available individual patient data were included in our meta-analysis. We compared rupture rates of women versus men using a Cox proportional hazard regression model adjusted for the PHASES score (Population, Hypertension, Age, Size of Aneurysm, Earlier Subarachnoid Hemorrhage From Another Aneurysm, Site of Aneurysm), smoking, and a positive family history of aneurysmal subarachnoid hemorrhage. Results: We pooled individual patient data from 9 cohorts totaling 9940 patients (6555 women, 66%) with 12 193 unruptured intracranial aneurysms, and 24 357 person-years follow-up. Rupture occurred in 163 women (rupture rate 1.04%/person-years [95% CI, 0.89–1.21]) and 63 men (rupture rate 0.74%/person-years [95% CI, 0.58–0.94]). Women were older (61.9 versus 59.5 years), were less often smokers (20% versus 44%), more often had internal carotid artery aneurysms (24% versus 17%), and larger sized aneurysms (≥7 mm, 24% versus 23%) than men. The unadjusted women-to-men hazard ratio was 1.43 (95% CI, 1.07–1.93) and the adjusted women/men ratio was 1.39 (95% CI, 1.02–1.90). Conclusions: Women have a higher risk of aneurysmal rupture than men and this sex difference is not explained by differences in patient- and aneurysm-related risk factors for aneurysmal rupture. Future studies should focus on the factors explaining the higher risk of aneurysmal rupture in women. Abstract : Supplemental Digital Content is available in the text.